Intelligence System during Muslim Rule: A Research Study in Contemporary Perspectives - Dr. Waleed Khan,; Dr. Kashif Mahmood, (Al Manhal Research Journal, 2022)
Intelligence system plays a vital role in the state security. This article is aimed at pointing out the modern intelligence methods in the light of islamic prespective. From the history of Islam especially from the Era of the Holy Prophet (PBUH), regimes of the right guided Caliphs and successor Muslim states Intelligence system of Muslim states has been elaborated in detail. In the Holy Quran and Seera of the Holy Prophet there are various guidelines to establish a successful intelligence system which is aligned with Islamic Shariah. The article presents the gradual evolution of intelliegence system of Islam and provides insight into contemporary needs and prospect developments in the field. The meothod research is narrative, analytical and applied. Basic sources as well as secondary sources are used to investigate into the subject matter. In the nut shell, the present article elaborates a composite scenario of the role of Intelligence system in Muslim rule.